Family Support System in Germany - an Example of the 2.0 Model - Zaborowska, Agnieszka (Studia Oeconomica Posnaniensia, 2019)
The purpose of the study is to characterize the family support system in Germany and to search for effective solutions that could be applied in the Polish welfare system. Social services in relation to family, similarly like other segments of the social welfare system in Germany, are based on the principle of individualization and on an institutional model that is practically implemented in an incentive and liberal concept. In addition, the support system is heavily based on the activities of non-governmental organizations. These are standards that make the social assistance system in Germany different from that of those in Poland. There are many elements which can be considered similar, but the foundations and fundamentals of the two systems are quite different. The material used for the study was collected during qualitative field tests carried out in Germany in Eichstätt in 2018. The author interviewed representatives of various professions from the family support system in Germany and representatives of the world of science who educate future social workers. Are the family support instruments used in Germany effective? What professions are responsible for helping the family? What solutions can be considered as key and could they be functional in Poland?